Nonadherence to Drugs among the Hypertensive Patients in Outpatient Department of a Secondary Hospital of Bangladesh (Cardiovascular Journal, 2019)
Background: One fifth Bangladeshi adults are hypertensive. Forty percent of them know that they are hypertensive. 53% to 75% hypertensive people have got uncontrolled hypertension. One of the most important causes of uncontrolled hypertension is nonadherence to drugs. We tried to find the causes of non adherence of drugs among the patients with HTN in a secondary care hospital of Bangladesh.Methods: The study was conducted from March 2018 to June 2018. Total 144 patients with HTN were included in the study. Taking drugs in less than 80% of the days of previous six months was defined as nonadherence. We used Hill Bone compliance scale to find out the causes of nonadherence to drugs.Results: Out of 144 patients 79 patients (55%) were non adherent to drugs. 36.8% patients forget to take their drugs, 34.02% patients run out of drugs, 29.86% patients miss taking drugs when they feel better, 15.27% patients skip their drugs before going to the doctor and 14.58% patients decide not to take drugs anymore without any specific reason. In most of the patients there are more than one causes of nonadherence. 85.9% patients with nonadherence had uncontrolled hypertension and 66.6 % of the nonadherent patients had target organ damage. Nonadherence is more in elderly patients and with increased duration of hypertension.Conclusion: Fifty five percent of the diagnosed hypertensive population is nonadherent to their drugs. We must take measures to diagnose HTN among our population and find the ways to make them adherent to their treatment.Cardiovasc. j. 2019; 11(2): 105-113